Development of a supply chain model for the production of biodiesel from waste cooking oil for sustainable development - Munir, M. Adeel; Imran, Shahid; Farooq, M.; Latif, Huma; Hussain, Amjad; Rehman, Ateekh Ur; Sultan, M.; Ali, Qasim; Krzywanski, Jaroslaw (Frontiers in Energy Research, 2023)
The increasing demand for energy and the severe environmental and economic repercussions have contributed to the development of renewables options. The scarcity of fossil fuels and their negative effect on the environment have sparked an alarming situation for alternative energy sources that are cleaner and more sustainable. Waste cooking oil is a valuable feedstock for biodiesel production, but it is often disposed of improperly, causing environmental pollution and health hazards. The current waste cooking oil supply chain in Pakistan and other countries is fragmented, inefficient, and often unregulated, leading to a lack of standardization and quality control. The study aims to develop a comprehensive supply chain model that integrates waste cooking oil collection, transportation, processing, and biodiesel production to create a sustainable value chain that benefits the environment, the economy, and society as a whole. The proposed optimization approach reduces the total expenses associated with the activities of the biodiesel supply chain. Modified possibilistic chance constrained programming (MPCCP) is used as a solution technique to represent this uncertainty. The MPCCP model is solved with the assistance of Lingo 18.0, while fuzzy logic demand forecasting was done using MATLAB. Accordingly, the fuzzy logic designer (FLD) simulation was conducted to demonstrate the applicability and effectiveness of FLD simulation for the particular kind of issue being considered. The research, not only focuses on mitigating environmental and health risks associated with improper waste cooking oil disposal, resulting in reduced pollution and a cleaner environment but it also advocates for the efficient utilization of waste cooking oil as a valuable feedstock for biodiesel production, thereby promoting a more sustainable and renewable energy source. By optimizing supply chain activities and minimizing costs, the research contributes to enhancing economic growth and efficiency within the biodiesel industry. This research encourages further exploration and collaboration among researchers and stakeholders to expand the applications of the proposed model in waste management, renewable energy, and supply chain optimization.